2016
DOI: 10.1177/1071100716635560
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Randomized, Multi-centered Clinical Trial Assessing Safety and Efficacy of a Synthetic Cartilage Implant Versus First Metatarsophalangeal Arthrodesis in Advanced Hallux Rigidus

Abstract: Level I, prospective randomized study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
213
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(223 citation statements)
references
References 18 publications
4
213
1
5
Order By: Relevance
“…Each of these 4 questions was accompanied by a 100‐mm VAS, with the pain questions anchored by the statements “no pain” and “worst pain possible” and the stiffness questions anchored by the statements “not stiff at all” to “most stiff possible.” To avoid clustering of scores, no verbal descriptors at intermediate points were used . We chose VAS rather than numerical rating scales because the VAS have been used in 2 of the 4 clinical trials for this condition .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these 4 questions was accompanied by a 100‐mm VAS, with the pain questions anchored by the statements “no pain” and “worst pain possible” and the stiffness questions anchored by the statements “not stiff at all” to “most stiff possible.” To avoid clustering of scores, no verbal descriptors at intermediate points were used . We chose VAS rather than numerical rating scales because the VAS have been used in 2 of the 4 clinical trials for this condition .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the high prevalence and burden of OA of the first MTP joint, relatively little research has been undertaken to evaluate commonly used treatments for this condition , and there is no consensus as to which outcome measures should be used to assess treatment effectiveness. Of the 4 randomized trials that have been undertaken to assess interventions for OA of the first MTP joint, 2 used generic visual analog scales (VAS) of pain , and 2 used the pain domain of the Foot Health Status Questionnaire (FHSQ) as the primary outcome measure. However, recent reviews of measures of foot function, foot health, and foot pain indicate that while several questionnaires have been developed, very few of these outcome measures have undergone adequate psychometric evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Baumhauer et al reported equivalent reduction in VAS pain scores and improvement in FAAM sports functional scores with the synthetic implant and first MTP arthrodesis. 35 Synthetic cartilage patients had an average of 4° of improvement in dorsiflexion and a revision rate of 9.2% to arthrodesis. While longer survivorship analysis is planned, this implant offers encouraging results.…”
Section: Operative Managementmentioning
confidence: 99%
“…Baumhauer et al[5] described the use of a synthetic cartilage implant as an allograft interpositional spacer. This synthetic cartilage implant (Cartiva, Inc., Alpharetta, GA, United States) is 8 or 10 mm in diameter and requires minimal bone and joint resection for implantation.…”
Section: Interpositional Arthroplastymentioning
confidence: 99%
“…Consequently, individuals with hallux rigidus experience joint pain and decreased range of motion (ROM) in the sagittal plane. This leads to altered gait mechanics and significant reduction in activity and quality of life for patients[4,5]. …”
Section: Introductionmentioning
confidence: 99%